Prevalence of Post-tonsillectomy Bleeding: A Case Series Study - Salem Farhat; Swelem, Muammer (AlQalam Journal of Medical and Applied Sciences, 2026)
Post-tonsillectomy haemorrhage is one of the most serious complications of tonsillectomy and remains a major concern for otolaryngologists due to potential morbidity and mortality. Although tonsillectomy has been widely practiced in Libya for decades, no published local data exists regarding post-tonsillectomy bleeding. This study aimed to evaluate the incidence and the pattern of post-tonsillectomy haemorrhage at Tripoli Central Hospital. The objective of this study is to determine the incidence of post-tonsillectomy haemorrhage and its association with demographic and surgical factors. A retrospective case series study was conducted, including 1,048 patients who underwent tonsillectomy or adenotonsillectomy between 2019 and 2024. Data collected included age, sex, type of surgery, and type of postoperative haemorrhage (primary or secondary). Statistical analysis was performed using SPSS version 16. Post-tonsillectomy haemorrhage occurred in 31 patients (2.9%). Primary haemorrhage was observed in 11 patients (35.5%), while secondary haemorrhage occurred in 20 patients (64.5%). Age showed a significant association with post-tonsillectomy bleeding, whereas the type of surgery did not. Post-tonsillectomy haemorrhage remains a significant clinical challenge. The bleeding rate observed in this study is comparable to those reported in the international literature. Older age was identified as a significant factor, while the type of surgery was not significant.